Reciprocal translocation, 4q-; 21p+, giving rise to Down's syndrome. - Jenkins, M B (1976)
A reciprocal translocation is described, t(4;21)(q27;p11), which occurs in a balanced carrier mother and her Down's syndrome child, 47,XX,t(4q-;21p+),+21. A review is presented of Down's syndrome associated with reciprocal translations involving chromosome No. 21.